2019
DOI: 10.1016/j.bjorl.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A new classification for septal perforation and effects of treatment methods on quality of life

Abstract: The septal perforation classification we propose would be beneficial for providing realistic dimensions, treatment methods, and surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…The flap had posterior wide pedicle. Our technique resembled the method used by Sapmaz et al 2018 [6] who had 95% successful results.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The flap had posterior wide pedicle. Our technique resembled the method used by Sapmaz et al 2018 [6] who had 95% successful results.…”
Section: Discussionmentioning
confidence: 75%
“…Fashioning of a good vascularized flap is one of the most important factors of success it should have a wide base, supplied with one of the main vessels, and big enough to cover the perforation and to be fixed with sutures without tension. If we compare different flaps, it was found that the best results were achieved by the superior flap based on ethmoidal arteries (100%) [6] and the posterior flap based on Sphenopalatine artery (95%) [7 and this study]. These arteries form the main supply of the nasal septum.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Es importante resaltar que ninguna de estas se trató de una complicación mayor. En cuanto a la infección del sitio operatorio, Kridel y colaboradores en 2018 reportaron tasas de 25 % cuando se usan injertos de dermis acelular (21,22); la cual es mayor en comparación con la obtenida con el uso del cartílago de banco reportada en este estudio (4,3 %). Sin embargo, es importante aclarar que no se encontró hasta la fecha otro estudio que describa la técnica quirúrgica con injertos de banco de tejidos.…”
Section: Discussionunclassified
“…granulomatous diseases, topical drug use (steroids and cocaine), bilateral nasal cauterization, nasal tampons, nose piercings. They are the most common anterior and rarely originate posterior and superior [6,7]. Septal perforation surgery is quite difficult.…”
Section: Discussionmentioning
confidence: 99%